The presidential appointee's handbook - DeSeve, G. Edward (Brookings Institution Press, 2017)
"A guide to competencies needed by the federal government's new top officials. The transition from one president to another, regardless of which party wins the 2016 elections, will mean many things, one of which is that some 3,000 to 4,000 new senior presidential appointees will take office in the first months of 2017. They will join some 6,000 members of the Senior Executive Service and nearly 1,000 admirals and generals already working in the top ranks of government. But the little-known truth is that the federal government has no formal, or even informal, continual learning program for its new high-level managers. If history is a guide, many of the next president's appointees will never have served in the federal government or, indeed, at any level of government. This means that they will need to hone their considerable skills to meet new challenges. This new, revised, and updated edition of the The Presidential Appointee's Handbook is intended to fill the need for learning by helping new presidential appointees develop the knowledge, skills, and capabilities they will need in their challenging assignments. Additionally, the new edition provides frameworks for success in areas such as strategic foresight, planning for results, risk management, and resilience that are designed to give appointees templates for achieving their goals. Blending theory with the demands of day-to-day practice, the book clarifies the roles and responsibilities of top government executives, helps them build a network of shared experiences and relationships, and lays out common competencies and codes of proper behavior for government leaders at all levels"--